PENGARUH REMUNERASI, BEBAN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PT JASA MARGA Tbk. - Luthfi Oetomo Ramadhan, (2022)
The type of research conducted by researchers is quantitative research which aims to determine the effect of remuneration on employee performance, the effect of workload on employee performance, the effect of career development on employee performance. As well as the effect of remuneration, workload and career development partially on employee performance. This research is a quantitative data with primary data sources. The population of this research is PT. Jasa Marga Tbk Indonesia. The sample used amounted to 81 respondents. The sampling technique uses non-probability sampling with purposive sampling method. Data collection was carried out by this study with an online questionnaire using the Google Form facility. This study uses the SEM method with the software used is SmartPls 3.0.